1992
DOI: 10.1002/polb.1992.090300913
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of inhomogeneous polyacrylamide hydrogels

Abstract: The physical and structural properties of acrylamide gels have been characterized by osmotic deswelling, mechanical compression, and x‐ray scattering. These properties vary considerably with the concentration of the crosslinking agent bisacrylamide, at fixed total monomers concentration (10% wt/wt water). In particular, changes in the properties appear more prominent at a crosslinking level of about 5‐6% (wt bisacrylamide/wt monomers). The compression modulus of as‐prepared and swollen gels passes through a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
180
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(190 citation statements)
references
References 23 publications
9
180
0
1
Order By: Relevance
“…Deviations from the ideal gel lead to clustering and clumping of microscopic regions of the less water-soluble bisacrylamide. Further support for the existence of microscopic (i.e., on the nanometer length scale) heterogeneities within polyacrylamide gels has been provided by light scattering studies (3,5,6). These studies indicate the existence of heterogeneous domains whose sizes vary with the amount of crosslinker.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Deviations from the ideal gel lead to clustering and clumping of microscopic regions of the less water-soluble bisacrylamide. Further support for the existence of microscopic (i.e., on the nanometer length scale) heterogeneities within polyacrylamide gels has been provided by light scattering studies (3,5,6). These studies indicate the existence of heterogeneous domains whose sizes vary with the amount of crosslinker.…”
Section: Introductionmentioning
confidence: 81%
“…These studies indicate the existence of heterogeneous domains whose sizes vary with the amount of crosslinker. As the crosslinker concentration increases, the scattering results have been interpreted as either the development of increasingly thicker fiber strands of acrylamide (5) or as increasing-diameter globular regions of less water-soluble bisacrylamide (3). The exact nature of these structures and the effects of crosslinker concentration on these structures have not been fully confirmed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhomogeneous static part represents a frozen structure, while the dynamic fluctuation presumably reflects diffusive relaxation. [6][7][8][9][10][11][12][13] The concept of the nonergodicity, stated by Pusey and Van Megen, 14 has led to the development of several relevant methods to analyze dynamic properties of gels. [15][16][17] To have a better understanding of the structure and the sol-gel transition of physical gels, we have developed a novel hydrogel, in which billions of small spherical swollen poly(N-isopropylacrylamide) (PNIPAM) microgels (∼100 nm) in a concentrated dispersion are jampacked into a macroscopic three-dimensional gel network.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the graft copolymers of acrylamide on different types of cellulose [8] revealed that various properties viz flocculation, solubility, thermal stability, binding strength, water retention and drag reduction effectiveness of the substrate increases. Besides these applications poly(acrylamide) has other multiple applications viz as polymer gel dosimeter [9], for water retention: owing to its high swelling capacity [10], in electrophoresis for separation of protein and DNA samples, as a model for drug delivery systems: for studying controlled drug release profiles [11][12][13].…”
Section: Introductionmentioning
confidence: 99%